Wheat stem sawfly oviposition preference and survivorship on winter wheat and downy brome - Altilmisani, Nuha Mustafa, author; Peairs, Frank, advisor; Ode, Paul, advisor; Bjostad, Louis, committee member; Byrne, Patrick, committee member (Colorado State University. Libraries, 2016)
The wheat stem sawfly Cephus cinctus Norton (Hymenoptera: Cephidae) is a major economic pest of wheat in the United States can decrease the yield and grain quality. Wheat stem sawfly infests both cultivated and uncultivated host plants. It is important to understand the oviposition behavior and host selection of the female wheat stem sawfly. Wheat stem sawfly selects the most suitable host for oviposition. The host selection behavior and oviposition preference of wheat stem sawfly for downy brome (Bromus tectorum L.) grass and winter wheat (Triticum aestivum L.) in Colorado was studied to assess whether downy brome is affecting the presence and infestation levels of wheat stem sawfly in winter wheat in northeastern Colorado. Infestation rates and larval development of the wheat stem sawfly were studied for two years (2013 and 2014) at seven commercial winter wheat fields and eight nearby downy brome sites in northeastern Colorado. Stem samples of each plant species were randomly collected per site weekly and sweep samples of sawfly adults were taken after adult emergence. Infestation rate in winter wheat was 12 to nearly 14 times higher than in downy brome throughout the two year survey. Larval mortality was twice as high in downy brome than in winter wheat over the two year survey. More adults were collected in May from winter wheat than from downy brome in the two year survey. Wheat stem sawfly females preferred to oviposit in wheat plants over downy brome. Female oviposition behavior influences by different host quality cues such stem height and diameter, volatile production, and growth stage. Host selection and oviposition preference by wheat stem sawfly females were studied with a combination of greenhouse choice and no-choice tests using a susceptible (hollow stem) winter wheat variety 'Byrd', a resistant (solid stem) winter wheat variety 'Bearpaw', and downy brome. Female sawflies in the no-choice tests laid similar numbers of eggs in Byrd and Bearpaw plants irrespective of growth stage, which were approximately 2.5 times the number of eggs laid on downy brome. Similarly, when given a choice, females laid similar numbers of eggs on Byrd and Bearpaw, but nearly twice as many eggs on either of these two cultivars than on downy brome. Females preferred to oviposit in larger diameter plant stems. However, stem height did not affect female preference for plants at growth stage Zadoks 49, but females prefered taller stems at growth stages Zadoks 32 and 60. Larval survivorship was lowest in the solid stem Bearpaw and was highest in downy brome and the hollow-stem Byrd. Hollow stem wheat had the highest larval survivorship. Female wheat stem sawflies use chemical cues from plants to identify a suitable host for oviposition. A Y-tube bioassay was developed to evaluate female wheat stem sawfly behavior in response to an airflow that passed over winter wheat cultivars and downy brome. Choice and no-choice tests were conducted with three host plants: wheat cultivars Byrd and Bearpaw and downy brome at three different growth stages: Zadoks 32, 49, and 60. Adult females were attracted to wheat cultivars Byrd and Bearpaw over downy brome at all growth stages. Downy brome was least preferred (31.82%) by female wheat stem sawfly in choice test of Bearpaw vs. downy brome at Zadoks 32 while it was equally preferred (49.21%) in the choice test of ‘Byrd vs. downy brome' at growth stage of Zadoks 60. The female's response speed did not differ when given a choice between the two wheat cultivars Byrd and Bearpaw. However, females were faster in making a choice (100% ≈ 86% females made fast choice) toward each of wheat cultivars over downy brome in the choice tests of Bearpaw vs. downy brome and Byrd vs. downy brome at all growth stages.
Keywords: larval survivorship; solid-stem; winter wheat; oviposition preference; downy brome; wheat stem sawfly